Westonci.ca is your go-to source for answers, with a community ready to provide accurate and timely information. Discover the answers you need from a community of experts ready to help you with their knowledge and experience in various fields. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
[tex]x^2-6x+6=0\\
x^2-6x+9-3=0\\
(x-3)^2=3\\
x-3=\sqrt 3 \vee x-3=-\sqrt3\\
x=3+\sqrt3 \vee x=3-\sqrt3[/tex]
[tex]x^2-6x+6=0 \\ \\a=1, \ \ b=-6, \ \ c=6 \\\\\Delta =b^2-4ac = (-6)^2 -4\cdot1\cdot 6 = 36-24=12\\\\\sqrt{\Delta }=\sqrt{12}=\sqrt{4\cdot 3}=2\sqrt{3}\\ \\x_{1}=\frac{-b-\sqrt{\Delta} }{2a}=\frac{6-2\sqrt{3}}{2 }=\frac{2( 3- \sqrt{3})}{2}= 3- \sqrt{3}\\\\x_{2}=\frac{-b+\sqrt{\Delta} }{2a}=\frac{6+2\sqrt{3}}{2 }=\frac{2( 3+ \sqrt{3})}{2}= 3+ \sqrt{3}[/tex]
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.